Respostas
respondido por:
0
Boa tarde
a - 1 = 998
a² + 1 = 998002
998*998002 = 996005996
E = (x⁴ - 1)/(a - 1)*(a² + 1)
E = (x⁴ - 1)/996005996
a - 1 = 998
a² + 1 = 998002
998*998002 = 996005996
E = (x⁴ - 1)/(a - 1)*(a² + 1)
E = (x⁴ - 1)/996005996
nathaliagalvan1:
Obg
respondido por:
0
Olá !!! :)
a - 1 = 998
a ² + 1 = 998002
998 * 998002 = 996005996
E = ( x ⁴ - 1 ) / ( a - 1 ) * ( a ² + 1 )
E = ( x ⁴ - 1 ) / 996005996
Abraços !!! :)
a - 1 = 998
a ² + 1 = 998002
998 * 998002 = 996005996
E = ( x ⁴ - 1 ) / ( a - 1 ) * ( a ² + 1 )
E = ( x ⁴ - 1 ) / 996005996
Abraços !!! :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás